Shariah Accounting In The Perspective Of Maqashid Shariah: "a Theoretical and Practical Study" - Siti Khodijah, Siti Khodijah; Madnasir; Suhendar (International Journal of Economics (IJEC), 2025)
The rapid development of Islamic economics in Indonesia demands an accounting system that is comprehensively with Islamic principles. This study aims to analyze the integration of Islamic accounting with Maqashid Sharia to produce a holistic and authentic accounting framework. Using a qualitative approach with a descriptive-interpretive design, this study involved 32 informants from practitioners, academics, regulators, and scholars in Jakarta, Yogyakarta, and Surabaya through in-depth interviews, document analyses, and participant observations. The results show that the implementation of Islamic accounting in Indonesia is still partial, with 78% of practitioners understanding only two of the five dimensions of Maqashid Sharia (hifz al-mal and hifz al-din), while a significant epistemological gap was found where 89% of practitioners still use the conventional accounting framework with minimal modification. The study successfully developed the Maqashid-based Holistic Performance Model (MHPM), which integrates the five dimensions of maqashid sharia in performance measurement, with model validation showing a 34% increase in stakeholder trust and 73% of institutions reporting improvements in more ethical governance. This study recommends a paradigm transformation from a compliance-based approach to a substance-based approach, the development of an integrated curriculum, the establishment of a Center of Excellence, and regulatory reform to support the implementation of Sharia accounting based on Maqashid Sharia, which can become a global role model.